(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Status epilepticus (SE) is a medical and neurologic emergency. Rapid and aggressive treatmentis required to prevent neuronal damage, systemic complications and death. Standardized treatment guidelines may improve the quality of emergency managementof SE. Objectives: The objective of the present study was to assess under lying causes of seizure and the immediate outcome of treatment following the specific proposed management protocol care. Methodology: This cross-sectional study was undertaken on 94 consecutive cases admitted inPediatrics department of Dhaka Medical College Hospital, Dhaka diagnosed as convulsive status epilepticus, age<15 years from September, 2012 – February, 2013. Cases were treated with specific institutional protocol. Under lying causes, outcome of the treatment and side effects of the drugs used were analyzed. Results: Among 94 cases, most of the patients belonged to 6 months - 5 years (73.34%), M: F was1.17:1. The leading presenting features were fever (75.53%), headache (36.17%), meningeal irritation (22.34%).Major causes of convulsive status epilepticus were febrile convulsion (42.6%), meningitis (22.3%), and epilepsy (21.3%), more than two-third (71%) had GTCS, 29% had focal seizure. Most of them presented within 6 hours of convulsion and nearly half of the patient responded to per-rectal diazepam with complete recovery and without any residual problems. A very few cases developed immediate or late behavioral problems or residual neurological deficit like hemiplegiaand epilepsy. Conclusion: Establishing causative factors and early intervention with specific treatment protocol can make rapid seizure control with better outcome. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 33-37